2017
DOI: 10.3390/ijms18040882
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Effect of Low Doses of Acenocoumarol in the Course of Ischemia/Reperfusion-Induced Acute Pancreatitis in Rats

Abstract: Intravascular activation of coagulation is observed in acute pancreatitis and is related to the severity of this inflammation. The aim of our study was to evaluate the impact of acenocoumarol therapy on the course of acute pancreatitis induced in male rats by pancreatic ischemia followed by reperfusion. Acenocoumarol at a dose of 50, 100, or 150 µg/kg/dose was administered intragastrically once a day, starting the first dose 24 h after the initiation of pancreatic reperfusion. Results: Histological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
(50 reference statements)
7
30
0
1
Order By: Relevance
“…We have also found that pretreatment with low doses of acenocoumarol resulted in a significant reduction of serum IL-1β concentration and limitation of AP severity. These important findings are consistent with an earlier report on the acenocoumarol-related reduction in IL-1β release in ischemia/reperfusion-induced AP and indicate that acenocoumarol is a universal protective agent in AP [34]. …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We have also found that pretreatment with low doses of acenocoumarol resulted in a significant reduction of serum IL-1β concentration and limitation of AP severity. These important findings are consistent with an earlier report on the acenocoumarol-related reduction in IL-1β release in ischemia/reperfusion-induced AP and indicate that acenocoumarol is a universal protective agent in AP [34]. …”
Section: Discussionsupporting
confidence: 93%
“…Induction of AP by cerulein administration led to reduction of pancreatic DNA synthesis by around 45% and this effect was reversed by pretreatment with low doses of acenocoumarol. This our result is similar to that observed in rats pretreated with acenocoumarol before induction of AP evoked by pancreatic ischemia followed by reperfusion [34] showing that pancreatoprotective effect of acenocoumarol is independent of primary cause of AP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In a recent experimental study, pretreatment with low doses of acenocoumarol, a vitamin K antagonist, attenuated ischemia/reperfusion-induced AP and was associated with reduced leukocyte inflammatory infiltration of the pancreas as well as diminished pancreatitis-induced increase in serum IL-1β concentrations [198]. The results were confirmed in another model of experimental AP, i.e., cerulein-induced AP in rats [199].…”
Section: Therapeutic Effects Of Anticoagulants In Acute Pancreatitismentioning
confidence: 84%